2019
DOI: 10.1016/j.tipsro.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging sequence evaluation of an MR Linac system; early clinical experience

Abstract: Objective(s): To systematically identify the preferred magnetic resonance imaging (MRI) sequences following volunteer imaging on a 1.5 Tesla (T) MR-Linear Accelerator (MR Linac) for future protocol development. Methods: Non-patient volunteers were recruited to a Research and Ethics committee approved prospective MR-only imaging study on a 1.5T MR Linac system. Volunteers attended 1-3 imaging sessions that included a combination of mDixon, T1w, T2w sequences using 2-dimensional (2D) and 3-dimensional (3D) acqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…The results of this study showed that the difference between the motion range detection capability of 4D-CT and 4D-MRI was not statistically significant when using 13 patient respiratory traces to generate pseudo-realistic phantom motion. While the use of MRI for detection, staging and surveillance of early stage lung cancer is well established [16], with recent developments in MR-guided radiotherapy [17][18][19][20], MRI simulators and the move toward MRI only workflows, results such as those reported in this study, which show equivalence between MRI and CT techniques, may be particularly relevant.…”
Section: Discussionmentioning
confidence: 90%
“…The results of this study showed that the difference between the motion range detection capability of 4D-CT and 4D-MRI was not statistically significant when using 13 patient respiratory traces to generate pseudo-realistic phantom motion. While the use of MRI for detection, staging and surveillance of early stage lung cancer is well established [16], with recent developments in MR-guided radiotherapy [17][18][19][20], MRI simulators and the move toward MRI only workflows, results such as those reported in this study, which show equivalence between MRI and CT techniques, may be particularly relevant.…”
Section: Discussionmentioning
confidence: 90%
“…SBE has been successfully applied to brachytherapy training [35] , [36] , [37] and training in on-call treatments [38] , but to the authors’ knowledge this is a novel use of SBE, and is well-suited to the nature of SMART. With the rise of MR-guided radiotherapy, healthy volunteer scans play a critical role in sequence and workflow optimization [39] , [40] , as well as providing a non-clinical training environment. Similar SBE workflows could be utilized to train residents prior to involvement in patient cases.…”
Section: Discussionmentioning
confidence: 99%
“…As the second institution to enter this UK study, the recruitment process and methodology followed that as described previously by Eccles and Smith et al [32] . Recruitment of suitable non-patient volunteers was achieved across the institution via email.…”
Section: Methodsmentioning
confidence: 99%
“…However, sequences used for RT guidance require additional considerations, further diverging their distinct properties from diagnostic equivalents. They need to be acquired in treatment position, be comparatively short in duration to facilitate patient compliance and minimise intrafractional motion, and furthermore sustain a high geometric fidelity over a relatively large field of view [32] . Additionally, the physical requirement for the receive coil to be suspended above the patient to be as close to, but not deform the body contour increases standoff [22] .…”
Section: Introductionmentioning
confidence: 99%